Electro-osmotic screening of the DNA charge in a nanopore - Luan, Binquan; Aleksei Aksimentiev (Phys Rev E Stat Nonlin Soft Matter Phys, 2008)
Extensive all-atom molecular dynamics simulations were performed to characterize the microscopic origin of the force experienced by DNA in a bulk electrolyte and a solid-state nanopore when subject to an external electrostatic field E. The effective screening of the DNA charge was found to originate from the hydrodynamic drag of the electro-osmotic flow that is driven by the motion of counterions along the surface of DNA. We show that the effective driving force F in a nanopore obeys the same law as in a bulk electrolyte: F=ximuE , where xi and mu are the friction coefficient and electrophoretic mobility of DNA, respectively. Using this relationship, we suggest a method for determining the effective driving force on DNA in a nanopore that does not require a direct force measurement.
Keywords: DNA; Models, Theoretical; Nanostructures; Osmosis; Static Electricity; Water